Prácticas que tienen las madres al preparar las loncheras de sus hijos/as Escuela Mariana Gutiérrez de Hidalgo, San Pedro. - Zhumio Guamán, Jeny Jackeline (2013)
Food is one of the key determinants of the health of people in all stages of life , one of which is the pre-school period , ranging from three to five years, in which an important social development is presented , cognitive and emotional as suitable and crucial moment for introducing healthy eating habits that will ultimately have a significant impact on nutritional status. During preschool children spend many hours in school, it is necessary to send food through the lunch box, in order to meet their nutritional needs, improve their academic performance and develop healthy eating habits. However, the inadequate preparation of the lunch box that includes foods high in calories and low in nutrients such as candy, salty chips, soft drinks and bottled juices are contributing to the development of obesity , tooth decay and allergies , among others by the excessive amount of preservatives and preservative . The greatest economic development, along with the food and culinary technological advancement, the incorporation of women to work outside the home , the new family structure , the great influence of advertising and television , the earliest entry of children to school, along with greater choice without adequate parental supervision menus , among other conditions a consumption of foods with high calories and low nutritional quality . The results from another study indicate that the group of breads and cereals that make up carbohydrates as energy carriers are the most consumed by children without neglecting energy intake that offers candy, very important part of your diet and food preferences . Once the fair nutrition and focus groups to assess perceptions and characterize the degree of knowledge of mothers were able to obtain positive changes in regard to nutrition education and could ensure that children can down new preparations as wash barley rice with ripe banana and rainbow salad íris . Among the factors that influence upon the selection of food is the economic factor , as reporting mothers often must make great efforts to select nutritious foods , and most valued products from the area and those foods that planted in home gardens , many of them have a business purpose and which makes them are intended for household consumption , but the influence of mass media such as television directly involved in the selection of food by children just prefer high-calorie foods completely oblivious to reality and the consequent emergence of diseases in later.